Prevalence of Cysticercosis in Pigs and Risk Assessment Among Occupationally Exposed Workers in Benue State, Nigeria - Alex A. Adikwu; Tyonginengen Iorparegh; Felix M. Per; Andrew M. Adamu; Olajide A. Owolodun; Paul F. Horwood; Theophilus I. Emeto; Oyelola A. Adegboye (Veterinary Medicine and Science)
ABSTRACT Aim Cysticercosis is a key zoonotic disease burden, posing significant public health challenges. Neurocysticercosis, a sequela associated with the larval stage of Taenia solium, is a recognised cause of late‐onset epilepsy in humans, thereby highlighting the need for robust epidemiological data. This study investigated the prevalence of cysticercosis in slaughtered pigs within Makurdi, Benue State, Nigeria, to contribute to understanding the disease's local epidemiology and associated risk factors. Methods From January to August 2019, we examined pig carcasses at four abattoirs: Utyondo market, Wurukum abattoir, Modern market, and Railway abattoirs. Structured questionnaires were administered to butchers, pig farmers, and civil servants to gather information on disease knowledge. A total of 2,176 pig carcasses were examined. Results Among the examined carcasses, 24 (1.1%) were infected. Of these, 18 (0.83%) were boars, and 6 (0.28%) were sows. The highest prevalence was observed in Utyondo market (2.75%), followed by Wurukum (0.77%) and Railway markets (0.65%). The diaphragm (odds ratio (OR) = 0.09; 95% confidence interval (CI): 0.01‐0.70) and the tongue (OR = 0.18; 95% CI: 0.04‐0.81) were less likely to be infected compared to the shoulder. Knowledge of cysticercosis was relatively high across all participants (71.72%, 95% CI: 61.77‐80.31). Conclusion Our findings indicate the endemicity of porcine cysticercosis in Makurdi abattoirs. While knowledge of the disease seems relatively widespread among exposed populations, gaps exist in understanding transmission routes. A collaborative One Health approach involving studies on occupationally exposed individuals is recommended for a comprehensive understanding of the disease burden and to develop targeted control strategies.